First assessment of biofouling assemblages in the northern Red Sea, an important region for marine non-indigenous species transfer - Juan Sempere-Valverde; Eva Aylagas; Vitaly Syomin; Marcos A. L. Teixeira; Glafira D. Kolbasova; Sofía Ruiz-Velasco; Sahar Chebaane; Arthur Anker; João Curdia; Ronald Cadiz; Dylan M. Cottrell; Andrea Desiderato; et al. (Frontiers in Marine Science, 2025)
Introduction Maritime traffic and coastal urbanisation significantly contribute to the introduction and proliferation of non-indigenous species (NIS). However, the lack of information might prevent effective monitoring in data-limited regions, particularly in areas experiencing demographic growth, where monitoring biofouling communities could offer crucial insights into the dynamics of NIS invasions. This study represents a baseline characterization of the biofouling communities in the northern Saudi Arabian Red Sea (NEOM region) prior to extensive urban, industrial, and commercial development. Methods Samples were collected in November 2023 and February 2024 from seven sites within the region. At each site and time, three settlement structures, each with a PVC panel attached to a brick and rope, were sampled after 3-months deployment. Panels were analysed with photo quadrat analysis (PhQd), examined to manually collect sessile macroinvertebrate specimens for taxonomic identification using morphological and DNA barcoding analysis, and scraped for bulk DNA analyses using DNA metabarcoding. Five water samples were also collected for environmental DNA (eDNA) analysis. The environmental characteristics of each site were obtained by deploying temperature data loggers and through an environmental risk assessment. Results Community patterns observed from the PhQd and bulk DNA datasets revealed a clear separation of two sites within Sharma lagoon from the remaining sites. The eDNA analysis of seawater confirmed these spatial differences, also detecting a variation between sampling times that was not observed with the other approaches. A total of 20 NIS and 18 cryptogenic species were recorded, from which 12 were identified morphologically and the remaining detected with molecular methods only. The generally low NIS coverage confirms that the NEOM region is less affected by marine biological invasions compared to other anthropized habitats within the Red Sea. However, sites in the Sharma lagoon showed high human pressure levels and comparatively higher coverage of cryptogenic bryozoans on panels. Discussion This study provides the first detailed assessment of biofouling communities in NEOM, establishing a baseline and contributing to a regional species reference library for non-indigenous and cryptogenic species. As coastal development spreads, it presents both challenges and opportunities, highlighting the need for sustainable, ecosystem-based approaches to protect valuable natural areas. This baseline is essential for future monitoring of biofouling dynamics as the region develops.

Rebuilding A Collapsed Bivalve Population, Restoring Seagrass Meadows, and Eradicating Harmful Algal Blooms In A Temperate Lagoon Using Spawner Sanctuaries - Christopher J. Gobler; Michael H. Doall; Bradley J. Peterson; Craig S. Young; Flynn DeLaney; Ryan B. Wallace; Stephen J. Tomasetti; Timothy P. Curtin; Brooke K. Morrell; Elizabeth M. Lamoureux; Berry Ueoka; Andrew W. Griffith; et al. (Frontiers in Marine Science, 2022)
During the past century, bivalve populations across the globe have collapsed, resulting in negative ecosystem consequences due to their outsized impact on shallow estuaries. In response, there has been strong interest in the restoration of marine bivalve populations. Here, we present a decade-long restoration effort that sought to rebuild a collapsed (99.5% reduction in harvest) and recruitment-limited population of hard clams ( Mercenaria mercenaria ) in Shinnecock Bay, NY, USA, using spawner sanctuaries: no-harvest zones where adults were planted at high densities (~27 m- 2 ). Between 2012 to 2019, more than 3.2 million clams were planted in 64 discrete sanctuary plots (~1,850 m 2 each) located in zones with maximal larval retention and sediment and seawater characteristics that would maximize the conditioning and spawning of adults. Hydrodynamic models, quantification of hard clam larvae, and spatial recruitment patterns demonstrated larvae spawned within sanctuaries were transported to regions where clam densities significantly increased 18-fold over seven years (2015-2021; p <0.001) and harvests significantly increased more than 16-fold over nine years (2012-2021; p <0.0001). Increases in populations and harvests were caused by smaller clams recruited within the time frame of the creation of spawner sanctuaries. Higher clam densities caused biological filtration times of the bay to decrease from up to three months at the start of the project to as low as 10 days in 2021. Concurrently, concentrations of the harmful brown tide alga, Aureococcus anophagefferens , and chlorophyll a significantly decreased ( p <0.005) while water clarity and the extent of seagrass beds significantly increased ( p <0.05). Increases in clam landings and improvements in water quality were not observed in adjacent lagoonal estuaries where restoration did not occur. Given these outcomes and the global need for rebuilding marine life, the implementation of spawner sanctuaries using the criteria set forth herein may be a promising approach for restoring hard clam and other bivalve populations in estuaries elsewhere.